Optimal design of pre-triggering airbag system for occupant protection performance during frontal crashes. (September 2019) - Xiao, Zhi; Wang, Li; Mo, Fuhao; Zhao, Siqi; Liu, Cuina
With the rapid development of car crash sensing and identification technology, the application of pre-triggering airbag system is becoming an important option to improve vehicle safety. Thus, the present study aims to investigate the injury protection ability of pre-triggering airbag system and optimize its performance in frontal crashes regarding the key physical parameters. A driver restraint system model established and validated by National Crash Analysis Center was employed and validated for studying the injury protection ability of pre-triggering airbag system. Then, the influences of airbag triggering time, airbag volume scaling factor, inflator mass flow, and exhaust orifice size of pre-triggering airbag system on driver's head and chest injuries were analyzed. Finally, the weighted injury criterion was selected as the evaluation index to optimize the pre-triggering airbag system. The results show the pre-triggering airbag should be designed with a larger airbag volume and inflator mass flow rate and smaller exhaust orifice. The optimized restraint system design presents a reduction of weighted injury criterion values in 100% and 40% overlapped frontal impacts reaching 25.63% and 42.23%, respectively.